High-throughput measurement of the content and properties of nano-sized bioparticles with single-particle profiler - Sezgin, Erdinc; Sych, Taras; Schlegel, Jan; Barriga, Hanna; Ojansivu, Miina; Hanke, Leo; Weber, Florian; Bostancioglu, R. Beklem; Ezzat, Kariem; Stangl, Herbert; Plochberger, Birgit; Laurencikiene, Jurga; et al. (Karolinska Institutet, 2023)
This item containst data sets for Sych et al, Nature Biotechology, 2023.

It contains raw fluroescence fluctuation data as excle sheet and raw figure files.

Abstract:

We introduce a method, single-particle profiler (SPP), that provides single-particle information on the content and biophysical properties of thousands of particles in the size range 5-150 nm. We apply SPP to measure the mRNA encapsulation efficiency of lipid nanoparticles, viral binding efficiency of different nanobodies, and biophysical heterogeneity of liposomes, lipoproteins, exosomes and viruses.

Data usage

Researchers are welcome to use the data contained in the dataset for any projects. Please cite this item upon use or when published. We encourage reuse using the same CC BY 4.0 License.

Data Content

FCS files as raw data (.fcs)

Excel and Prism files for graphs

# Software to open files:

.xlsx: Microsoft Excel

.pzfx: GraphPad Prism

.svg: Inkscape (https://inkscape.org/)

.fcs: Single Particle Profiler (https://github.com/taras-sych/Single-particle-profiler)

.ipynb: Jupyter Notebook, installed as part of anaconda platform, python 3.8.8 (https://www.anaconda.com/)

.py: executed via anaconda platform, python 3.8.8 (https://www.anaconda.com/)
Keywords: Analytical biochemistry; Synthetic biology; Industrial biotechnology diagnostics (incl. biosensors); Nanobiotechnology; Medical and Health Sciences; Medicin och hälsovetenskap; Biological Sciences; Biologi; Biochemistry; Biokemi